Business Activity on the Internet: Main Sources and Prospects of Legal Regulation - L. V. Shvarts (Теоретическая и прикладная юриспруденция)
The current Russian legislation defines the Internet as a kind of information and telecommunication network. The article is devoted to the problems of legal regulation of business use of the Internet. One of the main issues today in the context of relations “business — Internet” is the question of the ratio of the application of existing legislation and the adoption of special regulations that take into account the specifics of the world wide web. According to the author, there is no need to give a special status to the conclusion and execution of transactions through the Internet space, adopting special laws, it is enough to develop the provisions of existing ones, developing a mechanism for the use of Internet technologies.